Leading continuous change : navigating churn in the real world - Pasmore, William A. (Berrett-Koehler Publishers, Inc., 2015)
"Most change efforts fail because most change methods are built to deal with single challenges in a nice, neat, linear way. But leaders know that today, pressures for change don't come at you one at a time; they come all at once. It's like riding a roller coaster: sudden drops, jarring turns, anxious climbs into the unknown. Drawing on his years of experience at the Center for Creative Leadership and Columbia University, Bill Pasmore offers a four-part model and four mindsets that allow leaders to deal with multiple changes simultaneously without drowning in the churn."--